2001
DOI: 10.1097/00005537-200110000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Modified Evans Blue Dye Procedure and Video Nasal Endoscopic Evaluation of the Swallow

Abstract: The results of the current investigation suggest that the MEBD, at best, should be viewed only as a screening tool for the presence of gross amounts of aspiration in patients with a tracheostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
3
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 27 publications
0
24
3
6
Order By: Relevance
“…After the initial bolus presentations with the tracheotomy tube in place, the tracheotomy tube was removed and subglottal viewing through the tracheostoma was completed (Fig. 2) as previously described [13]. Briefly, the endoscope was inserted into the stoma site and was flexed upward to obtain a view of the subglottal structures and then turned downward to view the bronchial tree in order to confirm tracheal aspiration.…”
Section: Subjectsmentioning
confidence: 99%
“…After the initial bolus presentations with the tracheotomy tube in place, the tracheotomy tube was removed and subglottal viewing through the tracheostoma was completed (Fig. 2) as previously described [13]. Briefly, the endoscope was inserted into the stoma site and was flexed upward to obtain a view of the subglottal structures and then turned downward to view the bronchial tree in order to confirm tracheal aspiration.…”
Section: Subjectsmentioning
confidence: 99%
“…Several authors [76][77][78][79][80] have compared the accuracy of dye studies with those of VSS and FEES. Three studies [76][77][78] have reported a false negative rate of 50-61% but specificities near 100%. In these studies, foods of various consistencies for VSS or FEES were dyed blue and the tracheostomy tube was then suctioned.…”
Section: Dye Studiesmentioning
confidence: 99%
“…Since blue is not a color found in oropharyngeal secretions, blue dye has been used to detect aspiration without feeding trials [2], as well as added to enteral feedings of critically ill patients [3,4] and to oral feedings of patients with suspected dysphagia [5,6], for over 25 years. New concerns, however, have developed over both the safety [1,[7][8][9] and sensitivity [10][11][12] of blue dye use.…”
mentioning
confidence: 99%
“…Objective analyses, however, found that the blue dye method had poor sensitivity, i.e., a high false positive rate, for detecting aspiration in both enterally fed patients [3,20,21] and during dysphagia evaluations [10][11][12]. Although the FDA recommended 12 mg/kg/day as the limit for oral FD&C Blue No.…”
mentioning
confidence: 99%
See 1 more Smart Citation